Lo cotidiano como objeto de problematización en la narrativa fantástica: una lectura ideológica - Gregori, Alfons (Studia Romanica Posnaniensia, 2024)
Within the framework of the cognitive approach to the perception of reality distinguishing between grounds and figures, the main aim of this article is to study the foreground of fantastic stories, corresponding to elements of everyday life, unlike the figure, which usually is the preternatural motive. Thus, in this work the vision of everyday life proposed by the philosopher Bruce Bégout and the concept “ways of doing” created by the thinker Michel de Certeau will also be applied, as well as settled contemporary theories of the fantastic. As an illustration of all this, three Spanish short stories presenting ideological significance and written in different periods will be analyzed: La muerte de Capeto by V. Blasco Ibáñez, La resucitada by E. Pardo Bazán, and Reliquias by A. Martínez Castillo.